Sistematización de la EAPEAT del 55° Festival de la Leyenda Vallenata, en Valledupar - Cesar. Insumo creativo en la cátedra Montaje Interdisciplinar Teatro, Fiesta y Carnaval con la creación del montaje “Las tres preguntas del diablo enamorado” 2022-I. (2023)
The present work is the sistemation from the living experience at 55th Vallenato legend festival, As a point of arrival, the staging of the interdisciplinary theater, fest and carnival assembly chair 2022-1 was obtained with the work "Las tres preguntas del diablo enamorado" written and directed by Misael Torres. From the experience lived in Valledupar César, the students of the seventh semester of the degree in performing arts of the Antonio Nariño University make their own adaptation together with Maestro Alexander Llerena, having a creative process from innovation, transformation, the scenic feeling and the experiences that were elements of creation of the work.